All-solution based device engineering of multilayer polymeric photodiodes: Minimizing dark current - Keivanidis, Panagiotis E.; Khong, Siong Hee; Ho, Peter K.H.; Greenham, Neil C.; Friend, Richard H. (My University, 2009)
We present photodiodes fabricated with several layers of semiconducting polymers, designed to show low dark current under reverse bias operation. Dark current minimization is achieved through the presence of additional polymer layers that reduce charge carrier injection in reverse bias, when in contact with the device electrodes. All polymer layers are deposited via spin coating and are photocross-linked for allowing further polymer layer deposition, by using a bis-fluorinated phenyl-azide photocross-linking agent. Dark current density values as low as 40 pA/ mm2 are achieved with a corresponding external quantum efficiency (EQE) of 20% at a reverse bias of -0.5 V when an electron-blocking layer is used. Dark current is further reduced when both an electron- and a hole-blocking layer are used but the EQE falls significantly. © 2009 American Institute of Physics.
Keywords: Photodetectors; Electric currents; Photodiodes; Quantum efficiency; Materials; Photovoltaics; Spin coating; Short circuit; Conducting polymers; Heterostructures